2012
DOI: 10.1007/s10765-012-1247-4
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Radiometry Characterization of Limestone Rocks from the Península of Yucatán

Abstract: Limestone is a sedimentary rock composed of calcium carbonate with minor amounts of silica, iron oxide, clay, dolomite, and organic material. These types of stones have been used extensively as building materials. Due to this, determination of their thermal properties is of the utmost importance. These properties depend on the microstructure and composition of each type of rock. In this study, the effect of the thermal treatment of three different limestone rocks from the Peninsula of Yucatán were studied, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The value of the bulk density of the four rocks is between 1.98 g/cm 3 and 2.36 g/cm 3 (Table 1), which are lower than other values reported for limestone rocks [16,26,27]. A comprehensive study of porosity can provide valuable information to determine whether a given type of rock is susceptible to thermal stress or not.…”
Section: Physical Properties Of the Limestone Rocksmentioning
confidence: 77%
“…The value of the bulk density of the four rocks is between 1.98 g/cm 3 and 2.36 g/cm 3 (Table 1), which are lower than other values reported for limestone rocks [16,26,27]. A comprehensive study of porosity can provide valuable information to determine whether a given type of rock is susceptible to thermal stress or not.…”
Section: Physical Properties Of the Limestone Rocksmentioning
confidence: 77%
“…These results clearly show the effect of stone porosity on the susceptibility for fungal attack: although the visual inspection method of the surface and the averaging method of X-ray diffraction seemed to indicate that limestone B was more susceptible to fungal deterioration, most likely related to a different mineralogical composition, the SEM images demonstrate that the more porous limestone A is more prone to fungal deterioration up to much greater depths. It has been found that fungi are able to penetrate up to a depth of 4 to 9 mm, through cracks and microfissures of rock samples in stone buildings after 6 months of culture . In summary, limestone A has a higher porosity, hence, a high incidence of fractures and cavities was generally present, leading to more pronounced hyphae penetration.…”
Section: Resultsmentioning
confidence: 95%
“…It has been found that fungi are able to penetrate up to a depth of 4 to 9 mm, through cracks and microfissures of rock samples in stone buildings after 6 months of culture. 51 In summary, limestone A has a higher porosity, hence, a high incidence of fractures and cavities was generally present, leading to more pronounced hyphae penetration. In addition, because the TiO 2 -based coatings were characterized by a higher incidence of cracking, their performance in terms of hyphae penetrations was generally worse than for the ZnO-based coatings.…”
Section: Characterization Of Inoculated Stone Surfaces With Antifungalmentioning
confidence: 96%